Respuesta :

Answer:

6√3i.

Step-by-step explanation:

2√-27

= 2√9√-3

= 2*3√-3

= 6√3i.

The expression equal to 2√-27 is;

Option B: 6i√3

  • When dealing with complex numbers which are imaginary numbers, their square root is usually a bit different from when dealing with real numbers.

  • Now, in complex numbers square root is expressed as;

√-9 = 3i

This means that i² = -1

  • Now, we are given; 2√-27

The internal part can be simplified as;

2√(9 × -3) = (2 × 3)√(-3)

>> 6√-3

  • From earlier, we saw that;

i² = - 1

Thus;

6√-3 = 6√(-1 × 3)

>> 6√3i²

>> 6i√3

Read more at; brainly.com/question/11923802

ACCESS MORE

Otras preguntas